Low angle boundary migration of shot‐peened pure nickel investigated by electron channeling contrast imaging and electron backscatter diffraction. Issue 6 (28th January 2019) - Oh, Jin‐Su; Cha, Hyun‐Woo; Kim, Tae‐Hoon; Shin, Keesam; Yang, Cheol‐Woong
Abstract: Study on recrystallization of deformed metal is important for practical industrial applications. Most of studies about recrystallization behavior focused on the migration of the high‐angle grain boundaries, resulting in lack of information of the kinetics of the low angle grain boundary migration. In this study, we focused on the migration of the low angle grain boundaries during recrystallization process. Pure nickel deformed by shot peening which induced plastic deformation at the surface was investigated. The surface of the specimen was prepared by mechanical polishing using diamond slurry and colloidal silica down to 0.02 μm. Sequential heat treatment under a moderate annealing temperature facilitates to observe the migration of low angle grain boundaries. The threshold energy for low angle boundary migration during recrystallization as a function of misorientation angle was evaluated using scanning electron microscopy techniques. A combination of electron channeling contrast imaging and electron backscatter diffraction was used to measure the average dislocation density and a quantitative estimation of the stored energy near the boundary. It was observed that the migration of the low angle grain boundaries during recrystallization was strongly affected by both the stored energy of the deformed matrix and the misorientation angle of the boundary. Through the combination of electron channeling contrast imaging and electron backscatter diffraction, the threshold stored energy for the migration of the low angle grain boundaries was estimated as a function of the boundary misorientation. Abstract : Behavior of low angle grain boundary during recrystallization was directly observed. Shot‐peening process produces linear plastic deformation gradient. Total dislocation density was obtained using combination of electron backscatter diffraction and electron channeling contrast imaging. Threshold driving force for low angle grain boundary migration was evaluated.